The Effect of Inquiry-Based Learning on Eighth-Grade Students’ Descriptive Writing Skills at SMP Negeri 10 Palu - Sitti Nuraeni; Wahyudin Wahyudin; Desrin Lebagi; Budi Budi (Journal of General Education and Humanities, 2026)
This study investigates the effectiveness of Inquiry-Based Learning (IBL) in improving descriptive writing skills of eighth-grade students at SMP Negeri 10 Palu. A quasi-experimental design was employed involving 52 students selected through purposive sampling and divided into an experimental group and a control group. Both groups were given pre-tests and post-tests to measure their writing performance. The results show that the experimental group’s mean score increased from 60.54 to 75.88, while the control group also improved from 62.12 to 72.04. The independent-samples t-test showed no significant difference in pre-test scores between the two groups, indicating that both groups had similar initial writing ability. Although both groups showed improvement after the learning process, the experimental group showed a greater increase in mean score than the control group. The findings suggest that Inquiry-Based Learning contributed positively to students’ development of descriptive writing.